A Multispecies Fungal Biofilm Approach to Enhance the Celluloyltic Efficiency of Membrane Reactors for Consolidated Bioprocessing of Plant Biomass - Xiros, Charilaos; Studer, Michael H. (Frontiers in Microbiology, 2017)
The constraints and advantages in cellulolytic enzymes production by fungal biofilms for a consolidated bioconversion process were investigated during this study. The biofilm cultivations were carried out in reactors designed for consolidated bioprocessing (Multispecies Biofilm Membrane reactors, (MBM)) where an aerobic fungal biofilm produces the lignocellulolytic enzymes while a fermenting microorganism forms the fermentation product at anaerobic conditions. It was shown that although mycelial growth was limited in the MBM reactors compared to submerged cultivations, the secretion of cellulolytic enzymes per cell dry weight was higher. When Trichoderma reesei was used as the sole enzyme producer, cellobiose accumulated in the liquid medium as the result of the deficiency of β-glucosidase in the fungal secretome. To enhance β-glucosidase activity, T. reesei was co-cultivated with A. phoenicis which is a β-glucosidase overproducer. The two fungi formed a multispecies biofilm which produced a balanced cellulolytic cocktail for the saccharification of plant biomass. The mixed biofilm reached a 2.5 fold increase in β-glucosidase production, compared to the single T. reesei biofilm. The enzymatic systems of single and mixed biofilms were evaluated regarding their efficiency on cellulosic substrates degradation. Washed solids from steam pretreated beechwood, as well as microcrystalline cellulose were used as the substrates. The enzymatic system of the multispecies biofilm released four times more glucose than the enzymatic system of T. reesei alone from both substrates and hydrolysed 78% and 60% of the cellulose content of washed solids from beechwood and microcrystalline cellulose, respectively.